Model Kesetimbangan Pada Adsorpsi Ion Kadmium (Cd2+) Menggunakan Hidroksiapatit Dengan Variasi Suhu Adsorpsi Dan Kecepatan Pengadukan - Nissa, Aidina Fahrun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Metal pollution of cadmium (Cd+2) waters in causes a huge negative impact to people life. One of the ways to eliminate and minimize the metal content of cadmium is by the process of adsorption. The objective of this research is to study the effect of temperature and string rate as well as determination of equilibrium model in the cadmium ion adsorption using hydroxyapatite (HAp) as the adsorbent. Cadmium (Cd+2) solution with 3 mg/l was added with 0.5 g of HAp in a glass beaker with stirring rate of 100 rpm, 200 rpm, and 300 rpm at temperature 30Â°C, 40Â°C and 50Â°C. Cadmium concentration in the liquid was analyzed using AAS. The adsorption capacity of HAp adsorbent adsorption (Qe) decreased when the adsorption temperature increased. The calculation result of absorption capacity (Qe) at stirring rate of adsorption 100 rpm at temperature of adsorption 50Â°C, 40Â°C and 30Â°C were 0.687 mg/g, Qe 0.690 mg/g and 0.691 mg/g respectively. The adsorption capacity (Qe) of adsorbent HAp increased as stirring rate adsorption increased. The adsorption capacity (Qe) of cadmium at temperature adsorption 30Â°C for stirring rate of 300 rpm, 200 rpm, and 100 rpm were 1,132 mg/g, 1,023 mg/g, and 1,023 mg/g respectively. Adsorption mechanism of cadmium (Cd2+) with HAp is suitable with Freundlich isotherm model that represent the physical adsorption capacity of the heat of adsorption (ÎH) of -1.665304 kcal/mol.K and entropy change (ÎSÂ°) of 15.76 J/mol. K.Keywords: adsorption, cadmium (Cd2+), equilibrium model, hydroxyapatite